Redefining space pharmacology: bridging knowledge gaps in drug efficacy and safety for deep space missions - Barchetti, Karen; Derobertmasure, Audrey; Boutouyrie, Pierre; Sestili, Piero (Frontiers in space technologies, 2024)
The space environment is incredibly hostile, and humans are vulnerable in such conditions. Astronauts encounter various stress factors during a space journey, including radiation, microgravity, forceful acceleration during launch, altered magnetic fields, and confinement. These stressors significantly impact the human body homeostasis, leading to physio-pathological adaptations, loss of bone density, muscle atrophy, cardiovascular deconditioning, alterations in liver function, vestibular adaptations, and immune system dysregulation. These alterations can potentially influence drug pharmacokinetics and pharmacodynamics, affecting the efficacy and safety of medications administered to astronauts. Due to the limited number of studies on pharmaceuticals conducted in microgravity conditions, it’s challenging to assess the effectiveness and stability of these medications during spaceflight. The objective of the present work is to compare the state-of-the-art knowledge on PK/PD changes and factors likely to affect them during spaceflight, with the subjective perception of the problem by a collection of separate interviews conducted with seven experts in the field. The interviewees were chosen as “experts,” i.e., representatives in a specific discipline, who possess knowledge and experience in space pharmacology, physiology, or biology. Thus, our panel included astronauts, space surgeons, and scientists aiming to bridge the lack of experimental data in the literature. Each interview explores assorted aspects of space physiology and pharmacology, including drug use and storage onboard the ISS; notable consideration has arisen regarding the current research gaps and future space expeditions. All the interviews were held remotely using online conferencing software. None of the interviewees could provide a comprehensive overview regarding potential changes in drugs PK/PD in microgravity conditions. Further, any medication brought on board (whether as part of an astronaut’s medical kit or stored in the ISS pharmacy) is destroyed, thereby suppressing the possibility of analyzing any degradation products resulting from long-term exposure to microgravity and radiation. According to these results, the use of drugs without understanding how they are genuinely absorbed, distributed, metabolized, and excreted in microgravity conditions is concerning, posing risks for drug effectiveness. Conducting genotyping and phenotyping on astronauts would be beneficial for developing personalized pharmacological countermeasures for each astronaut and anticipating expected drug metabolism changes during space missions.